Pengurusan Penjualan Saham Sebagai Objek Harta Kekayaan dalam Boedel Afwezigheid - Natasha, Shela; Rahman, M. Taufik (Fakultas Syariah INSURI Ponorogo, 2022)
The protection of civil rights for every citizen, including those who are absent (afwezigheid) is one of the rights that must be fulfilled by the government. The interpretation of the rule of law is basically needed to realize the objectives of the law, namely justice, expediency, and legal certainty. Not explicitly stated in the law as an object of boedel afwezigheid's assets, it should not be a barrier for the Balai Harta Peninggalan as boedel management to carry out the management of the shares. Expansion of wealth that is not just land and buildings as stated in the rules governing afwezigheid is absolutely necessary to provide legal certainty in the management and management of the share boedel. Therefore, this research which combines literature study and field study was conducted to explain the management of sales as an object of property in the boedel afwezigheid conducted by the Heritage Heritage Center so that it can be seen that the implementation of legal rules in the field can be more flexible than written legal rules.